Analysis of Frame Construction Strength in Belt Conveyor Design Using Ansys Workbench - Anggi Pratama; Delvis Agusman (Sainteks: Jurnal Sain dan Teknik, 2023)
Belt conveyor is a material transfer machine that is generally used in the industrial world to transport semi-finished production materials and products from one part to another. In making a conveyor belt, the main component is needed, namely the frame. The frame is a construction that functions as a place where the components become a unit on a machine. In this research, a simulation test will be carried out to determine the strength of the construction and the material used by the framework for component loading by providing maximum carrying capacity for variable loading. The loading given is 100kg, 200kg, 300kg, 400kg and 500kg. This test simulation uses the Ansys Workbench 2020 R2 software with the finite element analysis (FEA) method. Analysis of strength testing uses a frame model measuring 4070 mm x l500 mm x 2440 mm as the main frame which is then simulated with maximum loading variations ranging from 100 – 500kg. The analysis results from testing the strength of the construction of the conveyor belt frame against the loading variable, obtained a safety factor of 100kg = 3.70; 200kg = 3.01; 300kg = 2.67; 400kg = 2.41; 500kg = 2.16. The minimum safe limit for dynamic loads is 2 according to Dobrovolsky's "machine element" book, thus the maximum loading tolerance for the conveyor belt frame may not be more than 500 kg.